Jemmy Jock Bird. - Jackson, John C., 1931-2015 (University Of Calgary Press, 2004)
Jemmy Jock Bird, the son of a Cree woman and an English trader employed by the Hudson's Bay Company, has become part of the mythology of the mountain man era. In this creative non-fiction account, Jackson meticulously reconstructs the life of this intriguing individual who was caught between opposing sides of a dual M?tis heritage. Closely identified with the Cree and the Peigan, Bird's trading activities and undercover work as a "confidential servant" of the Hudson's Bay Company during the competitive period of the fur trade are explored using materials from the Hudson's Bay Company Archives, the Montana Historical Society, and Bird's descendants living on the American Blackfeet Reserve in Browning. As an interpreter, Bird was later instrumental in negotiating the 1855 Blackfoot peace treaty and the 1877 Canadian Treaty 7. Jackson steeps himself in the sparse documentation of the fur trade era to shed some much-needed light on Jemmy Jock Bird's adventurous career - one that straddled the international borders of the northern plains and mountain west and touched upon many aspects of western development.